Na11Sn2PS12: a new solid state sodium superionic conductor. Issue 1 (12th December 2017) - Zhang, Z.; Ramos, E.; Lalère, F.; Assoud, A.; Kaup, K.; Hartman, P.; Nazar, Linda F.
Abstract : Elucidation of the structure of a new sodium superionic conductor, Na11 Sn2 PS12 via single crystal XRD and AIMD simulations reveal isotropic 3D Na + -ion conduction pathways. Abstract : We report a new sodium superionic conductor, Na11 Sn2 PS12, that crystallizes in an unprecedented three-dimensional structure type and exhibits an ionic conductivity of 1.4 mS cm −1, with a very low activation energy barrier for Na-ion mobility of 0.25 eV. A combination of structural elucidation via single crystal X-ray diffraction and ab initio molecular dynamics simulations show that Na + -ion conduction pathways flow through equi-energetic sodium–sulfur octahedra interconnected by partial vacancy cross-over sites in all crystallographic dimensions, providing an understanding of the underlying isotropic 3D fast-ion conduction in this material.